Necesidad de establecer en el reglamento a la Ley de Servicio Público disposiciones específicas que permitan sancionar a la autoridad que dispuso un sumario administrativo sin fundamento o causales legales - Costa Sarango, Gloria Josefina (2015)
The institutions of the State permanently humbled by behaviors illegitimate political actors that they violate the stability and internal governance reflect not only the weakening of democracy but that undermine legal certainty that in addition to being one of our most important assets, represent the emblem of protection and certainty that we have the inhabitants to expect the repair of our rights when somehow have been affected. The organic law of public service, in its Art.44 determines that the administrative proceedings is "the administrative, oral and reasoned process by which public administration determined or not the Commission of administrative offences laid down in the present law, a servant or public servant. Your procedure it will regulate in the General regulations of this law. The administrative proceedings will be implemented in application of the guarantees due process, respect for the right to defense and the principle that in case of doubt will prevail as more favorable to the server or server. Determine administrative responsibilities, imposed the sanctions referred to in this law. Establish civil or criminal liability, the appointing authority will be transfer to the competent organs of Justice.While law contentious administrative in its article 5 was established; "The administrative resolutions cause state when they are not susceptible to any resource in the administrative, are definitive or mere formality, if they decide, directly or indirectly, the merits of the case, so that put an end to that or make impossible its continuation. The problem of protecting standards of the legal order against its violation by legal persons of a public nature, is extremely difficult to solve in practice, because it is equivalent to find a means to make the force, power, is fastened by the right, by the legal order. The individual guarantees that with the title of individual establishing our Constitution, properly refer to any subject that has or may have the character of ruled in the terms in which we exposed this. In Ecuador, in similar manner to all treated models, the Constitution of the Republic does not consider any express rule where it is established that the Constitutional Court is the Supreme interpreter of the Constitution. However, this feature can be inferred it several standards, in a similar way as it has happened in models such as constitutional supremacy, norms of the Constitution, and constitutional jeopardy A particular note in the Ecuadorian case, however, is the lack of clarity of the cited standards. While it is true, the principles of supremacy and regulations are specified in the 2008 Constitution, they are not the clear enough, they do not have a preferred location in the structure of the Constitution and appear as isolated from the whole. In addition, they do not bind these rules to the Constitutional Court as responsible for establishing these principles through its rulings Hence the need for an inquiry, where convenience is parsed establish specific provisions which allow sanction to the authority that laid out administrative proceedings without foundation in the regulations under the public service act or causal legal, with which will ensure better the rights of public servants